Perancangan Sistem Informasi Pemasok Barang Rongsokan Dengan Pendekatan User Centered Design - Ningsih, Tri Adi; Widiartha, I Made; Suhartana, I Ketut Gede; Putra, I Gusti Ngurah Anom Cahyadi (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2024)
Information systems play a crucial role in facilitating business processes, including in the scrap recycling industry. In this context, this research aims to develop an information system that enables efficient management of the procurement process of scrap materials from suppliers. The User Centered Design (UCD) method is adopted to ensure that the developed system truly meets the needs and preferences of users. The system implementation is carried out using web-based technologies with PHP and MySQL as the database backend. End users, including scrap material suppliers, can access the system through a responsive web interface. System evaluation is conducted using the Single Ease Question (SEQ) and System Usability Scale (SUS) methods to measure user responses and system usability. The development results show that the scrap material supplier information system has been successfully developed. Users responded positively to the user-friendly interface and provided functionality. The testing involved 10 respondents, yielding a SEQ score calculation of 88%, indicating success. Additionally, SUS testing resulted in a high satisfaction level of 87.25% among users regarding system usability. Thus, this research contributes to the development of information systems that integrate UCD principles to support efficiency and effectiveness in managing scrap material suppliers in the recycling industry.